The fragments of the work of Heraclitus of Ephesus on nature - Heraclitus, Ephesius 550 v.Chr.-480 v.Chr (N. Murray, 2011)
"The latest writers on Heraclitus, namely, Gustav Teichmüller and Edmund Pfleiderer, have thought it necessary to preface their works with an apology for adding other monographs to the Heraclitic literature, already enriched by treatises from such distinguished men as Schleiermacher, Lassalle, Zeller, and Schuster. That still other study of Heraclitus, however, needs no apology, will be admitted when it is seen that these scholarly critics, instead of determining the place of Heraclitus in the history of philosophy, have so far disagreed, that while Schuster makes him out to be a sensationalist and empiricist, Lassalle finds that he is a rationalist and idealist. While to Teichmüller, his starting point and the key to his whole system is found in his physics, to Zeller it is found in his metaphysics, and to Pfleiderer in his religion. Heraclitus' theology was derived, according to Teichmüller, from Egypt; according to Lassalle, from India; according to Pfleiderer, from the Greek Mysteries. The Heraclitic flux, according to Pfleiderer, was consequent on his abstract theories; according to Teichmüller, his abstract theories resulted from his observation of the flux. Pfleiderer says that Heraclitus was an optimist; Gottlob Mayer says that he was a pessimist. According to Schuster he was a hylozoist, according to Zeller a pantheist, according to Pfleiderer a panzoist, according to Lassalle a panlogist. Naturally, therefore, in the hands of these critics, with their various theories to support, the remains of Heraclitus' work have suffered a violence of interpretation only partially excused by his known obscurity. No small proportion of the fragments, as will be seen in my introduction, have been taken in a diametrically opposite sense. Recently a contribution towards the disentanglement of this maze has been made by Mr. Bywater, an acute English scholar. His work (Heracliti Ephesii Reliquiae, Oxford, 1877) is simply a complete edition of the now existing fragments of Heraclitus' work, together with the sources from which they are drawn, with so much of the context as to make them intelligible. Under these circumstances I have thought that a translation of the fragments into English, that every man may read and judge for himself, would be the best contribution that could be made. The increasing interest in early Greek philosophy, and particularly in Heraclitus, who is the one Greek thinker most in accord with the thought of our century, makes such a translation justifiable, and the excellent and timely edition of the Greek text by Mr. Bywater makes it practicable. The translations both of the fragments and of the context are made from the original sources, though I have followed the text of Bywater except in a very few cases, designated in the critical notes. As a number of the fragments are ambiguous, and several of them contain a play upon words, I have appended the entire Greek text. The collection of sources is wholly that of Mr. Bywater. In these I have made a translation, not of all the references, but only of those from which the fragment is immediately taken, adding others only in cases of especial interest"--Preface. (PsycINFO Database Record (c) 2010 APA, all rights reserved)